Caregiver experiences of feeding children with developmental disabilities: a qualitative study using interpretative phenomenological analysis from India - Reema Samuel; Bhuvaneswari Manikandan; Paul Swamidhas Sudhakar Russell (BMJ Open, 2023)
Objective We aimed to explore caregiver experiences of feeding children with developmental disabilities, in the context of it being influenced by biological, personal and social factors.Design This study applied a qualitative study design through focus group discussions (FGDs), using interpretative phenomenological analysis. Data were analysed using thematic content analysis.Setting This study was conducted at the Child Psychiatry Unit of a tertiary care centre in South India, between March and November 2020.Participants Seventeen mothers of children with developmental disabilities, who provided written informed consent, participated in four FGDs.Results Three over-arching themes were identified. Feeding experience: (a) a tedious, confusing task; (b) disproportionate onus on mothers; (c) influenced by sociocultural norms.Conclusion Feeding can be a stressful activity for both caregiver and child, influenced by family structure and sociocultural belief systems. Considering caregivers’ emotional status, facilitatory and hindering environmental factors, and actively exploring strategies to promote the generalisation of strategies learnt into real-life outcomes are essential in tailoring deficit-specific feeding interventions.